2015
DOI: 10.1158/1078-0432.ccr-14-2035
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anti-CD22 Anthracycline-Based Antibody–Drug Conjugate (ADC) That Overcomes Resistance to Auristatin-Based ADCs

Abstract: Purpose: We are interested in identifying mechanisms of resistance to the current generation of antibody-drug conjugates (ADC) and developing ADCs that can overcome this resistance.Experimental Design: Pinatuzumab vedotin (anti-CD22-vc-MMAE) and polatuzumab vedotin are ADCs that contain the microtubule inhibitor monomethyl auristatin E (MMAE) attached to the antibody by the proteasecleavable linker maleimidocaproyl-valine-citrulline-p-aminobenzoyloxycarbonyl (MC-vc-PAB). Early clinical trial data suggest that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 13 publications
3
127
1
3
Order By: Relevance
“…In a similar fashion, cell line models made resistant to CD22-or CD79b-targeting ADCs employing the vcMMAE linker-payload remained sensitive to the respective ADCs delivering a different payload (e.g., PNU-159682; ref. 29). Thus, by swapping each module of an ADC with a different functional group, ADC activity can be modulated.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar fashion, cell line models made resistant to CD22-or CD79b-targeting ADCs employing the vcMMAE linker-payload remained sensitive to the respective ADCs delivering a different payload (e.g., PNU-159682; ref. 29). Thus, by swapping each module of an ADC with a different functional group, ADC activity can be modulated.…”
Section: Discussionmentioning
confidence: 99%
“…1D). A similar linkerpayload for maleimide-based conjugation to thiols, referred to as NMS249, has recently been described and was evaluated in the context of a CD22-specific ADC (33).…”
Section: Generation Of Anthracycline-based Linker-payloads For Sortasmentioning
confidence: 99%
“…PNU-159682 was described to be several orders of magnitude more potent than doxorubicin (34) and has recently shown promise as a payload for ADCs in the context of conventional chemical conjugation (32,33). Indeed, when conjugated to trastuzumab, a significantly increased cytotoxic activity was achieved in comparison with maytansine conjugates and even cells with moderate HER2 expression levels, that were not sensitive to Kadcyla, could efficiently be killed (Figs.…”
Section: In Vivo Antitumor Activity Of Cd30-specific Pnu Conjugatementioning
confidence: 99%
See 1 more Smart Citation
“…31,32 It has been reported that in some tumors with high multi-drug resistance (MDR) activity, PBD-conjugated ADCs can overcome the resistance mechanism and remain active in acute myeloid leukemia model. 33 We tested m906MMAF initially and compared it with m906PBD (data not shown), and found that the latter was more potent in killing IMR-05 cells.…”
Section: Discussionmentioning
confidence: 99%